New Quests in Stellar Astrophysics II: Ultraviolet properties of evolved stellar populations - Dagostino, Miguel Chavez (Springer, 2017)
The International Conference “Ultraviolet Properties of Evolved Stellar Populations” held in Puerto Vallarta, M ́exico on April 16-20, 2007, is the second ”New Quests in Stellar Astrophysics” event, sponsored by the Instituto Nacional de Astrof ́ısica, ́Optica y Electr ́onica (INAOE) and the University of Guadalajara (U. de G.). In 2001 we organized the first meeting aimed at stressing the importance of stellar physics to understand the properties of stellar systems at different scales. We have now focused on the ultraviolet interval to review our current knowledge on the properties of evolved stellar populations. The conference represented a unique opportunity to collect an up-to-date view of the outcomes from various satellites, from the long-lived International Ul-traviolet Explorer to current facilities, such as the Galaxy Evolution Explorer. This fresh panorama will undoubtedly impact on the reparation of planned ultraviolet space missions, such as the World Space Observatory and the Ultraviolet Imaging Telescope